Ectopic Lymphoid Structures: Powerhouse of Autoimmunity - Corsiero, Elisa; Nerviani, Alessandra; Bombardieri, Michele; Pitzalis, Costantino (Frontiers in Immunology, 2016)
Ectopic lymphoid structures (ELS) often develop at sites of inflammation in target tissues of autoimmune diseases such as rheumatoid arthritis, Sjögren’s syndrome, multiple sclerosis, myasthenia gravis and systemic lupus erythematosus. ELS are characterised by the formation of organized T/B cells aggregates which can acquire follicular dendritic cells network supporting an ectopic germinal center (GC) response. In this review, we shall summarise the mechanisms which regulate the formation of ELS in tertiary lymphoid organs, with particular emphasis on the role of lymphoid chemokines in both formation and maintenance of ELS, the role of emerging positive and negative regulators of ELS development and function, including T follicular helper cells and IL-27, respectively. Finally, we shall discuss the main functions of ELS in supporting the affinity maturation, clonal selection and differentiation of autoreactive B cells contributing to the maintenance and perpetuation of humoral autoimmunity.